1990
DOI: 10.1002/jor.1100080211
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of adult chondrocyte metabolism by a thyroid‐derived factor

Abstract: This paper reports the effects of adding partially purified bovine thyroid calcitonin, thyrocalcitonin, to adult bovine articular cartilage cells. Thyrocalcitonin stimulated chondrocyte proliferation fourfold under low serum (0.5%) culture conditions. In serum-free medium, thyrocalcitonin stimulated cell proliferation more than twofold. With high-density cultures in serum-free medium, chondrocyte glycosaminoglycan (GAG) synthesis was stimulated 60% by thyrocalcitonin. Cell-associated radioactivity was increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…While human articular chondrocytes subjected to T 3 in monolayer and serum containing medium showed enhanced proliferation [55], earlier studies showed no effect of T 3 or T 4 on adult bovine cartilage cell proliferation or GAG synthesis in high-density cultures in serum-free medium [56]. This is consistent with our findings of no difference between T 3 -treated chondrocytes vs. control in means of DNA and GAG content, and in line with other studies performed in serum-free medium [57].…”
Section: Discussionmentioning
confidence: 99%
“…While human articular chondrocytes subjected to T 3 in monolayer and serum containing medium showed enhanced proliferation [55], earlier studies showed no effect of T 3 or T 4 on adult bovine cartilage cell proliferation or GAG synthesis in high-density cultures in serum-free medium [56]. This is consistent with our findings of no difference between T 3 -treated chondrocytes vs. control in means of DNA and GAG content, and in line with other studies performed in serum-free medium [57].…”
Section: Discussionmentioning
confidence: 99%
“…The cells were washed two times in Dulbecco's phosphate buffered saline without Mg 2+ and Ca 2+ , washed once with DMEM, and then plated at 2.6 × 10 4 cells/cm 2 in DMEM containing FBS, gentamicin, and ascorbic acid (25 μg/ml) (Sigma Chemical, St. Louis, MO). High density monolayer cultures were tested in serum‐free medium containing 25 μg/ml gentamicin, 25 μg/ml ascorbic acid, 1 mM selenium, and a liposome supplement [Jones and Smith, 1990].…”
Section: Methodsmentioning
confidence: 99%
“…Serum-containing medium was removed 24 h prior to loading by washing in PBS ( 3 x ) and serum-free medium (DMEM/F12 supplemented with 30 mM HEPES. 0.01 M selenium, 25 pglml ascorbate, a lipid supplement and gentamicin) was added for an overnight incubation prior to loading [20].…”
Section: Cl7onfirocj~te Isolfltionmentioning
confidence: 99%